Association of early life adversity with cardiovascular disease and its potential mechanisms: a narrative review - Tan, Huiying; Zhou, Huiting; Chen, Jingmei; Ren, Huixia; Guo, Yi; Jiang, Xin (Frontiers in Public Health, 2024)
Strong epidemiological evidence has shown that early life adversity (ELA) has a profound negative impact on health in adulthood, including an increased risk of cardiovascular disease, the leading cause of death worldwide. Here, we review cohort studies on the effects of ELA on cardiovascular outcomes and the possible underlying mechanisms. In addition, we summarize relevant studies in rodent models of ELA. This review reveals that the prevalence of ELA varies between regions, time periods, and sexes. ELA increases cardiovascular health risk behaviors, susceptibility to mental illnesses, and neuroendocrine and immune system dysfunction in humans. Rodent models of ELA have been developed and show similar cardiovascular outcomes to those in humans but cannot fully replicate all ELA subtypes. Therefore, combining cohort and rodent studies to further investigate the mechanisms underlying the association between ELA and cardiovascular diseases may be a feasible future research strategy.